Calcifying cystic odontogenic tumor of anterior mandible - A case report with series of follow up radiographs - Hima John; S Padmashree; P S Shilpa; Sayyad Z Innus (Wolters Kluwer Medknow Publications, 2019)
The calcifying odontogenic cyst was first described by Gorlin et al. who were impressed by the presence of numerous ghost cells. Currently, this particular entity is known as calcifying cystic odontogenic tumor (CCOT). Since its recognition, the lesion is seen occurring both peripherally and centrally in the jaws. Its origin, pathogenesis, and histopathological variations have evoked considerable discussions in the past which has resulted in formulation of various classifications. This paper highlights a case of CCOT in the anterior mandible, the characteristic features, treatment and follow-up are discussed, emphasizing on the series of follow-up radiographs.